Dipstick Diagnosis of Neonatal Seizure Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
A dipstick test strip (Sulfistix) showing elevated urinary sulfite concentrations (400 mg/l) was used in diagnosis of molybdenum cofactor deficiency (MCD), an inborn errror of metabolism, in a male infant presenting with convulsions and cerebral dysgenesis at birth and followed for 3 years at the Klinik fur Kinder und Jugendmedizin, St Marlenhospital, Vechta, Germany.